2019
DOI: 10.4103/ams.ams_280_18
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma arising in the background of oral submucous fibrosis

Abstract: Introduction:Oral submucous fibrosis is a chronic debilitating condition with potential for malignant transformation. Squamous cell carcinoma arising from a background of oral submucous fibrosis presents clinically as a distinct disease due to different etiopathogenesis.Methodology:This prospective case series describes thirty cases of oral squamous cell carcinoma (OSCC) alongside oral submucous fibrosis (OSF). Patient clinical data were recorded including type and duration of habits, site of tumor, size, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Studies have also shown that the OSMF-associated OSCC has an earlier age of onset, more aggressive biological characteristics, and a higher rate of metastasis and relapse [ 92 ]. It was reported that OSCC caused by OSMF background follows different clinical manifestations, and malignant transformation occurs in younger age groups and has poorer prognosis [ 93 ]. The OSMF clinical classifications (concerning opening degree and degree of fibrosis) are not positively associated with the canceration rate due to insufficient evidence.…”
Section: Prognosis and Malignant Transformationmentioning
confidence: 99%
“…Studies have also shown that the OSMF-associated OSCC has an earlier age of onset, more aggressive biological characteristics, and a higher rate of metastasis and relapse [ 92 ]. It was reported that OSCC caused by OSMF background follows different clinical manifestations, and malignant transformation occurs in younger age groups and has poorer prognosis [ 93 ]. The OSMF clinical classifications (concerning opening degree and degree of fibrosis) are not positively associated with the canceration rate due to insufficient evidence.…”
Section: Prognosis and Malignant Transformationmentioning
confidence: 99%
“…23 Reduced proliferation index of the cells was described as an additional factor contributing to the reduction of epithelial thickness. 24 Fig. 4: Atrophic surface epithelium and degeneration of superficial muscle layers…”
Section: Atrophy Of Epitheliummentioning
confidence: 99%
“…(Figure 5) The atrophic epithelium, dysplasia and other genetic mutations occurring in OSMF make the mucosa susceptible to develop carcinogenetic changes. 24,25 Reduction in vascularity further reduces drainage of accumulated products from the tissue. This allows the carcinogens to remain in contact with the mucosa for a longer duration.…”
Section: Dysplasia and Malignant Transformationmentioning
confidence: 99%
See 2 more Smart Citations